Education in India : policy and practice - Jandhyala B.G. Tilak; Tilak, Jandhyala B.G. (London Sage, 2021)
"Education in India: Policy and Practice presents trends in shifting education policies in independent India and how the State, academia and civil society reacted to the changing priorities during the last 50 years. The 20 chapters, authored by eminent scholars and experts, provide valuable insights into complex policy issues at the grassroots as well as macro levels. The book discusses major challenges and concerns such as growth and inequalities, education of women, quality of higher education and research, and making policy reforms for the transformation of the system in such a way that it helps in broader social transformation. The issues analyzed have also been taken up in the editor's introductions, which provide a perspective on their wider social, political and economic implications in detail. This volume is an important reference tool for grappling with the challenges of the new National Education Policy 2020"--